Effectiveness of Development the Innovation of Photo Patch Category Play Activity to Develop Receptive Language and Expressive Language of Preschool-Aged Child - Maneesri, Rujiruth; Worasuk, Nattanan; Pitsachart, Nualyai (Journal of The Royal Thai Army Nurses, 2025)
This quasi-experimental pretest posttest design aimed to study the effectiveness of development the innovation of photo patch category play activity to develop receptive language and expressive language of preschool-aged child to compare the development of both aspects after using. The sample group consisted of 30 preschool children aged 4-5 years from Wat Bo-Ngern School, Lad Lum Kaew District, Pathum Thani Province, selected through purposive sampling. The research instruments included: 1) the innovation of photo patch category play activity and 2) a developmental assessment form for receptive language and expressive language of preschool-aged child with CVI values of 0.87 and 0.80 respectively, and reliability of 0.85. Data were analyzed using descriptive statistics and t-test statistics. The research results showed that language comprehension skills in shape categorization showed the greatest improvement, t = 8.95 - 9.85 at p<.001 level, while basic subtraction by shapes showed the least improvement, t = 4.68-5.12 at p<.01 level. For language use skills, answering “if hungry” questions showed t = 7.24 constant at p<.001 level, and explaining object functions showed t = 3.85 constant at p<.01 level.